Electrokinetic properties of the mammalian tectorial membrane - Ghaffari, Roozbeh (National Academy of Sciences, 2013)
The tectorial membrane (TM) clearly plays a mechanical role in stimulating cochlear sensory receptors, but the presence of fixed charge in TM constituents suggests that electromechanical properties also may be important. Here, we measure the fixed charge density of the TM and show that this density of fixed charge is sufficient to affect mechanical properties and to generate electrokinetic motions. In particular, alternating currents applied to the middle and marginal zones of isolated TM segments evoke motions at audio frequencies (1–1,000 Hz). Electrically evoked motions are nanometer scaled (∼5–900 nm), decrease with increasing stimulus frequency, and scale linearly over a broad range of electric field amplitudes (0.05–20 kV/m). These findings show that the mammalian TM is highly charged and suggest the importance of a unique TM electrokinetic mechanism.